2018
DOI: 10.1007/s00431-017-3073-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of allergies and performance in epinephrine auto-injector use: a controlled intervention in preschool teachers

Abstract: A single education session substantially improved preschool teachers' attitudes and knowledge in allergies and anaphylactic emergencies. Additionally, their practical performance in auto-injector administration increased. What is Known: • Food allergies are increasing among children. • The knowledge about allergies and anaphylactic emergencies is poor. What is New: • The proportion of teachers who felt well-prepared for an anaphylactic emergency increased after a single education session. • The proportion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 24 publications
7
45
0
5
Order By: Relevance
“…Saudi teachers had positive attitudes toward anaphylaxis, consistent with a published in Slovenia,[23] where a group of researchers studied future teachers’ attitudes and knowledge regarding the management of potential students and life-threatening allergic reactions. Additionally, Devetak et al reported that 85% of future teachers in Slovenia demonstrated a positive attitude towards learning more about the management of life-threatening allergic reactions in potential students.…”
Section: Discussionsupporting
confidence: 80%
“…Saudi teachers had positive attitudes toward anaphylaxis, consistent with a published in Slovenia,[23] where a group of researchers studied future teachers’ attitudes and knowledge regarding the management of potential students and life-threatening allergic reactions. Additionally, Devetak et al reported that 85% of future teachers in Slovenia demonstrated a positive attitude towards learning more about the management of life-threatening allergic reactions in potential students.…”
Section: Discussionsupporting
confidence: 80%
“…However, what is available at schools seems to be inconsistent and irregular. Previous studies evaluating the effect of training interventions have been successful at improving participant knowledge, self-rated confidence and reducing the clinical risk of reactions, which remain significant after 4-12-week follow-ups [12]. Yet, access to such training for schools is poor as standardised initiatives across institutions with secured funding for implementation seem to be lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Visitas regulares aos alergistas e prescrição de caneta de adrenalina atualizada (Cabrera et al, 2017;Feuille et al, 2017) foram ações apontadas como medida de segurança para criança, além da necessidade de administração de adrenalina precocemente (Dumeier et al, 2018;Song & Lieberman, 2019;Urrutia-Pereira et al, 2018), que pode ser garantido através de estoque de epinefrina nas escolas (Cabrera et al, 2017;DeSantiago-Cardenas et al, 2015;Moritz & Schoessler, 2018;Portnoy & Shroba, 2014;Schoessler & White, 2013;Steffens et al, 2017;Szychlinski et al, 2015;Tsuang & Wang, 2016;White et al, 2017;Zadikoff et al, 2014) e também pelo porte de auto injetores de adrenalina pelo estudante (Chipps, 2013;Solé et al, 2018).…”
Section: ) Melhorar a Segurança Dos Medicamentos Utilizados Nas Reaçunclassified
“…A maior parte dos artigos apontou a urgência na criação de Programas de Treinamento com cursos teórico-práticos para atendimentos de emergências nas alergias, anafilaxia para profissionais de educação (Chipps, 2013;Dumeier et al, 2018;Feuille et al, 2017;Juliá-Benito et al, 2017;Kao et al, 2018;Moritz & Schoessler, 2018;Murphy, 2014;Polloni et al, 2016;Portnoy & Shroba, 2014;Pouessel et al, 2017;Russell & Schoessler, 2017;Szychlinski et al, 2015;Tsuang et al, 2017;Tsuang & Wang, 2016;Urrutia-Pereira et al, 2018;Vale et al, 2015;Wahl et al, 2015), se estendendo também aos funcionários da cozinha e lanchonetes .…”
Section: ) Treinamento Em Primeiros Socorros E Plano De Emergênciaunclassified